A new ruthenium black dye design with improved optical properties for transparent dye sensitized solar devices. Issue 47 (13th November 2017) - Boaretto, R.; Carli, S.; Caramori, S.; Bignozzi, C. A.; Saccone, D.; Magistris, C.; Barolo, C.; Viscardi, G.
Abstract : A new ligand for panchromatic Ru(ii ) sensitizer yields 32% efficiency improvement over conventional "black dye" in transparent DSSCs. Abstract : We report here on the preparation and on the electronic properties of a panchromatic Ru(ii ) sensitizer based on a new ligand which allows for higher molar extinction coefficients in the visible and better performances (32% efficiency improvement) over conventional "black dye" in transparent DSSC.